From iconic handshapes to grammatical contrasts: Longitudinal evidence from a child homesigner - Coppola, Marie; Brentari, Diane (Frontiers in Psychology, 2014)
Many sign languages display crosslinguistic consistencies in the use of two iconic aspects of handshape, handshape type and finger group complexity. Handshape type is used systematically in form-meaning pairings (morphology): Handling handshapes (Handling-HSs), representing how objects are handled, express events with an agent (“hand-as-hand” iconicity), and Object handshapes (Object-HSs), representing an object's size/shape, are used to express events without an agent (“hand-as-object” iconicity). Second, in the distribution of meaningless properties of form (morphophonology), Object-HSs display higher finger group complexity than Handling-HSs. Some adult homesigners, who have not acquired spoken or signed language and instead use a self-generated gesture system, exhibit these two properties as well. We examined both structures over time in one child homesigner, “Julio”, age 7;4 (years; months) to 12;8. We elicited descriptions of events with and without agents to determine whether morphophonology and morphosyntax can develop without linguistic input during childhood, and their relative timing. Within this period: 1) Julio used handshapes differently in his responses to vignettes with and without an agent; however, his pattern differed from that seen in signers, adult homesigners, or gesturers: while he tended to use a Handling-HS for events with an agent (82%), he was less likely to use an Object-HS for non-agentive events (49%); 2) his Object-HSs showed higher finger group complexity than his Handling-HSs, as in previously studied signers and adult homesigners; and 3) these two levels of structure developed independently, with phonological structure showing a sign-like pattern at an earlier age than morphosyntactic structure. We conclude that iconicity alone is insufficient to explain the development of linguistic contrasts in homesign. These findings also highlight the importance of considering the distribution of forms within an emerging linguistic system.